Investing Even in Uneven Contests: Effects of Asymmetry on Investment in Contests. (6th March 2015) - Hart, Einav; Avrahami, Judith; Kareev, Yaakov; Todd, Peter M.
Abstract Many competitions, such as political campaigns, innovative endeavors, sports, or courting rituals, require investment of nonrefundable resources: One contestant wins the prize for the invested amount, whereas all others lose their investments without receiving compensation. Frequently, contests are asymmetric, because of differing resources or prize valuations. Does asymmetry discourage the weaker contestants from investing? Do stronger contestants take this into account and also invest less? Or does the desire to win abolish these differences? Two experiments explored the effects of asymmetry between the contestants—arising from their resources or prizes—on nonrefundable investments. Subjects repeatedly competed in both symmetric and asymmetric contests, enabling within‐subject comparisons. We observed an effect of asymmetry only when it concerned resources: Subjects overall invested less when their resources were unequal, whereas inequality in the prizes did not influence investments. This pattern suggests that winning itself is motivating. The changes between consecutive investments can be explained by reactions to the previous outcome (win or loss): Across all contests, investment decreased following a win and increased following a loss. Copyright © 2015 John Wiley & Sons, Ltd.